2020
DOI: 10.1002/brb3.1535
|View full text |Cite
|
Sign up to set email alerts
|

Different exercises can modulate the differentiation/maturation of neural stem/progenitor cells after photochemically induced focal cerebral infarction

Abstract: Introduction Exercise therapies during rehabilitation significantly promote recovery from various deficits after cerebral infarction, which is mediated by neuronal plasticity with distinct inputs. Although adult neurogenesis can also be modulated by neuronal activity before synaptogenesis, how distinct exercises contribute to the neurological reorganization of the injured cerebral cortex remains unclear. In the present study, we aimed to elucidate the effects of different exercise therapies on motor recovery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…The ischemic brain lesion can be easily assessed and monitored in this model by a real-time reduction in blood perfusion, which is validated by TTC-unstained brain tissue, which indicates the infarcted area. A recent preclinical study [35] in rats that used the photothrombotic stroke model demonstrated a 60-78% loss in uniform blood perfusion in the damaged area. A similar effect was observed in this study and other research by the group [17,26], and it was closely linked to sensorimotor deficit [9].…”
Section: Discussionmentioning
confidence: 99%
“…The ischemic brain lesion can be easily assessed and monitored in this model by a real-time reduction in blood perfusion, which is validated by TTC-unstained brain tissue, which indicates the infarcted area. A recent preclinical study [35] in rats that used the photothrombotic stroke model demonstrated a 60-78% loss in uniform blood perfusion in the damaged area. A similar effect was observed in this study and other research by the group [17,26], and it was closely linked to sensorimotor deficit [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative that the increase in endogenous NSPCs after cell‐based therapy must be followed up with not only an increased training but also an appropriate rehabilitation modality that would allow the immature endogenous and exogenous cells to properly mature and effectively integrate with the host tissue. Voluntary exercise, forced physical training, and EE have all been shown to improve motor function by increasing BDNF and neurogenesis, which is one of the main driving forces underlying stroke recovery 24,25,43,61 . However, behavioral task specificity and integration need to be more widely incorporated in experimental rehabilitation strategies to achieve better functional outcomes in stroke animals 39 …”
Section: How To Maximize Therapeutic Effect In a Combined Cell‐based ...mentioning
confidence: 99%
“…Aerobic exercise has been shown to increase BDNF and endogenous neurogenesis ( Mang et al, 2013 ). Forced low-intensity exercise increases NPC maturation and facilitates a more robust motor recovery ( Morishita et al, 2020 ). Most importantly, both EE and stem cell transplantation increase adult neurogenesis which has been implicated as the main driving force behind recovery ( Zhan et al, 2020 ; Garthe et al, 2016 ; Tajiri et al, 2103; Singhal et al, 2014 ; van Praag et al, 1999 ) The stem cells induce neuroprotection early and influence proliferation when the rodents are still in recovery.…”
Section: The Role Of Enriched Environment and Exercise In Enhancing N...mentioning
confidence: 99%